The function of knowledge audit in portal's faculty decision making - Sulaiman, Nor Intan Saniah; Alias, Rose Alinda (Universiti Utara Malaysia, 2005)
Knowledge Audit is one of the activities that should be conducted prior to development of a Knowledge Management System in an organization. There are three knowledge audit methods, includes Knowledge Survey, Knowledge Inventory and Knowledge Mapping. Knowledge audit facilitates identification of the various forms of knowledge that are required by stakeholders of a Knowledge Management System. However, despite its importance, a few KMS developers perform knowledge audit. Thus, the main objective of this study is to make decision to develop a faculty's portal that serves as a KMS as well as a knowledge auditor. The portal is developed specifically for academic staff and students in a faculty or school in university. This study is initiated with a questionnaire, which can be applied from Knowledge survey and can be used to identify explicit knowledge required by an academic community. The responses are used to develop the prototype for faculty's Knowledge Audit Portal. The portal can be as output that shows how knowledge required by a community of academic staff and student can be identified as the community uses a basic portal.